PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI PENDEKATAN SAINTIFIK PADA MATERI BANGUN DATAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Sari, Nanda Ayu Permata; Albab, M Ulul; Ilmayasinta, Nur (Discovery : Jurnal Ilmu Pengetahuan, 2023)
This study aims to determine the influence of the Problem Based Learning model through a scientific approach to flat building material to improve student learning outcomes. This study used quantitative research with Quasi Experimental design. This research was conducted at SMPN 1Sugio. The study sample was conducted using purposive sampling technique. Two classes were taken as research samples, namely class VII A as an experimental class and class VII B as a control class. Data collection techniques in this study used tests and non-tests. The test consists of pretest and posttest, while the non-test is in the form of a validation questionnaire for each question item. Data analysis techniques used in processing data are N-Gain, analysis prerequisite tests, and hypothesis tests. Based on the results of calculations that have been carried out, the average posttest value of the control class is 86, the average N-Gain value is 0.67 medium criteria. While the average posttest score of the experimental class was 88, the average N-Gain value was 0.73 high criteria. The results of the hypothesis test of the processed data produce the value of sig. (2-tailed) i.e. 0.011 so that rejected and accepted, meaning that there is an influence from the use of the Problem Based Learning model through a scientific approach to student learning outcomes.